AB1083 CURRENT PRACTICE AND OPINIONS ON IMAGING-GUIDED INTERVENTIONAL PROCEDURES IN RHEUMATIC AND MUSCULOSKELETAL DISEASES: INTERIM RESULTS OF A MULTINATIONAL MULTIDISCIPLINARY SURVEY TO INFORM EULAR POINTS TO CONSIDER. (2nd June 2020) - Carubbi, F.; Bosch, P.; Machado, P. M.; Scirè, C. A.; Alunno, A.; Baraliakos, X.; Dejaco, C.
Abstract : Background: maging is widely used for diagnostic purposes in patients with rheumatic and musculoskeletal diseases (RMDs). In recent years, it is increasingly used also to guide interventional procedures. However, the extent of imaging application for this purpose as well as the different technical standards employed across Europe are not known. Objectives: To learn how much imaging is used for interventional procedures in RMDs. To explore the technical standards employed in different settings and how important they are rated by users. Methods: As part of the work of a multidisciplinary EULAR Task Force to develop recommendations for the use of imaging to guide interventional procedures in patients with RMDs, a survey was developed. The survey explored aspects of different interventional procedures (e.g. joint aspiration/injection) such as the use of imaging guide and the technical standards. Respondents provided also a 0-10 rating of how important they considered the same conditions/items with regard to each procedure. The survey was distributed to: rheumatologists across Europe, USA, Central America, South America, Asia and Pacific Area, HPs across Europe, European and American associations of other specialities (e.g. radiology, anaesthesiology). The survey was launched in December 2019. Interim results after 4 weeks are presented. Results: 200 responses from 36 countries were collected. The respondents were mainly rheumatologists (90%) (Figure 1). 90% of respondents performed interventional procedures related to RMDs and of these, 76% use imaging guide. Ultrasonography (US) is the most commonly used technique (96%) followed by X-ray/fluoroscopy (13%). Among respondents using imaging guide, 60% received training on both imaging and imaging-guided procedures, 20% only on imaging and 16% no training. 49% of respondents perform the whole procedure using direct image guidance, 21% use imaging to find the appropriate anatomical landmark and then perform the procedure blindly. Air and contrast agent to control needle placement are rarely used (≤20%). Respondents provided also a rating (0-10) of how important they considered different technical conditions/items for each procedure and an estimate on a Likert scale of how often they used them for each of the procedures (Figure 1 shows an example). In most cases respondents use always/most of the times the conditions/items that they considered important. Discrepancies were mainly due to barriers at their own center. Conclusion: Imaging, mainly US, is widely used to guide interventional procedures. However, training is not homogeneous and the use of imaging guide as well as technical conditions are based on the operator's opinion/experience. This survey will inform the EULAR points to consider for the use of imaging to guide interventional procedures in patients with RMDs. Disclosure of Interests: Francesco Carubbi Speakers bureau: Francesco Carubbi received speaker honoraria from Abbvie and Celgene outside this work., Philipp Bosch: None declared, Pedro M Machado Consultant of: PMM: Abbvie, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Roche and UCB, Speakers bureau: PMM: Abbvie, BMS, Lilly, MSD, Novartis, Pfizer, Roche and UCB, Carlo Alberto Scirè: None declared, Alessia Alunno: None declared, Xenofon Baraliakos Grant/research support from: Grant/research support from: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Consultant of: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Speakers bureau: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Christian Dejaco: None declared